A three-dimensional method for the simulation of temperature fields induced by solar radiation. Issue 3 (February 2019) - Yan, Yihang; Wu, Dingjun; Li, Qi
The determination of temperature fields is usually required for the calculation of structural deformation and stress induced by temperature variation. To guarantee the serviceability and safety of structures by improving calculation accuracy, this study presents a three-dimensional structural temperature field simulation framework that accounts for shadowing effects and changes in solar radiation intensity throughout the day. Field experiments were conducted to update the established model and to verify the accuracy of the numerical algorithm. The proposed method was finally applied in a case study to determine the temperature fields of both a rail and a U-shaped concrete girder. The results show that the temperature field of the concrete girder had obvious nonlinear distribution characteristics. Three-dimensional structural temperature field analysis is especially required for complicated structures with varied sections along the longitudinal axis.